Assessment of sediment and water quality in the Owabi reservoir - Abankwa, Ernest (2012)
A thesis submitted to the Department of Environmental Science, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements of Master of Science, October-2010